Use of Gamma Radiation for the Genetic Improvement of Underutilized Plant Varieties - María de la Luz Riviello-Flores; Jorge Cadena-Iñiguez; Lucero del Mar Ruiz-Posadas; Ma. de Lourdes Arévalo-Galarza; Israel Castillo-Juárez; Marcos Soto Hernández; Carlos Roman Castillo-Martínez (Plants, 2022)
Agricultural biodiversity includes many species that have biological variants (natives, ecotypes, races, morphotypes). Their use is restricted to local areas because they do not fulfill the commercial requirements; however, it is well documented that these species are a source of metabolites, proteins, enzymes, and genes. Rescuing and harnessing them through traditional genetic breeding is time-consuming and expensive. Inducing mutagenesis may be a short-time option for its genetic improvement. A review of outstanding research was carried out, in order to become familiar with gene breeding using gamma radiation and its relevance to obtain outstanding agronomic characteristics for underutilized species. An approach was made to the global panorama of the application of gamma radiation in different conventional crop species and in vitro cultivated species, in order to obtain secondary metabolites, as well as molecular tools used for mutation screening. The varied effects of gamma radiation are essentially the result of the individual responses and phenotypic plasticity of each organism. However, even implicit chance can be reduced with specific genetic breeding, environmental adaptation, or conservation objectives.